Detection of local recurrence with 3-Tesla MRI after radical prostatectomy: a useful method for radiation treatment planning? - Bürgy, Daniel; Weidner, Anja; Lohr, Frank; Wenz, Frederik; Schönberg, Stefan; Attenberger, Ulrike (In vivo, 2018)
Background/Aim: Salvage radiotherapy improves biochemical control in patients with recurrence of prostate cancer after prostatectomy. Radiotherapy target volumes of the prostatic fossa are based on empirical data and differ between different guidelines. Localization of recurrence with multiparametric magnetic resonance imaging (MRI) might be a feasible approach to localize recurrent lesions. Patients and Methods: Twenty-one patients with biochemical recurrence after radical prostatectomy were included (median prostate-specific antigen (PSA) =0.17 ng/ml). Multi-parametric MRI was performed using a 3-T MR system. Results: Lesions were detected in seven patients with a median PSA of 0.86 ng/ml (minimum= 0.31 ng/ml). Patients without detectable recurrence had a median PSA of 0.12 ng/ml. All patients with detectable lesions responded to radiotherapy. Eleven out of 14 patients without detectable recurrence also responded. Plasma flow in suspicious lesions was correlated with PSA level. Conclusion: Detection of recurrence at the prostatic fossa with our approach was possible in a minority of patients with a low PSA level. Clinical relevance of plasma flow in suspicious lesions should be further investigated.
Gesehen am 04.10.2019